Maintenance tocolysis: a reappraisal of clinical evidence - Stelzl, Patrick; Kehl, Sven; Rath, Werner (Archives of Gynecology and Obstetrics, 2019)
Introduction: Maintenance tocolysis, mostly defined as the continuation of tocolytic treatment beyond 48 h, remains a matter of debate. There is no sufficient evidence from randomized controlled trials, that maintenance tocolysis is able to prolong pregnancy significantly and to reduce severe neonatal morbidity and mortality. Hence, it is not recommended in current guidelines. On the contrary, maintenance tocolysis is commonly used in clinical practice and subject of current clinical-scientific investigations. Tocolytics for maintenance treatment: None of the conventional tocolytics (beta-sympathomimetics, calcium-channel blockers, magnesium, cyclooxygenase inhibitors, and oxytocin receptor antagonists) have proven to be appropriate for maintenance treatment. Progesterone and 17-α-hydroxyprogesterone caproate have shown promising results in low-quality randomized trials, but not in high-quality studies. Discussion: Basically, the value of studies regarding maintenance tocolysis is limited by a considerable heterogeneity, its mostly low quality, significant differences in methodology as well as the inadequate statistical power due to the small number of women studied. So far, maintenance tocolysis is a case-by-case decision outweighing the benefits and harms of tocolytic treatment.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Efficacy; Maintenance tocolysis; Progesterone; Recommendations; Threatened preterm birth; Tocolytic agents